Increasing emergency hospital activity in Denmark, 2005–2016: a nationwide descriptive study. Issue 2 (12th February 2020) - Fløjstrup, Marianne; Bogh, Soren Bie; Henriksen, Daniel Pilsgaard; Bech, Mickael; Johnsen, Søren Paaske; Brabrand, Mikkel
Abstract : Objectives: To describe changes in unplanned acute activity and to identify and characterise unplanned contacts in hospitals in Denmark from 2005 to 2016, including following healthcare reform. Design: Descriptive study. Setting: Data from Danish nationwide registers. Population: Adults (≥18 years). Participants: All adults with an unplanned acute hospital contacts (acute inpatient admissions and emergency care visits) in Denmark from 2005 to 2016. Primary and secondary outcome measures: Outcomes were annual number of contacts, length of stay, number of contacts per 1000 citizen per year, age-adjusted contacts per 1000 citizens per year, sex, age groups, country of origin, Charlson Comorbidity Index score, discharge diagnosis and time of arrival. Results: We included a total of 13 524 680 contacts. The annual number of acute hospital contacts increased from 1 067 390 in 2005 to 1 221 601 in 2016. The number also increased with adjustment for age per 1000 citizens. In addition, regional differences were observed. Conclusions: Unplanned acute activity changed from 2005 to 2016. The national number of contacts increased, primarily because of changes in one of the five regions.